Abu Bakar As-Shiddiq’s Inauguration Speech: The Principles and Basics of His Leadership at the Time of Rashidun Caliphate - Zalikha Zalikha; Zhafira Zahra Tsabitah; Zalsabilah Nur Hanafie; Zulfa Nur Azizah (Haluan Sastra Budaya, 2024)
This study aims to analyze the meaning and leadership of Abu Bakr Ash-Siddiq in his speech at his inauguration. Leadership is a relationship and influence between the leader and the led. After the Prophet Muhammad's death, the leadership was replaced by Abu Bakr Ash-Siddiq and made him the first caliph of the Muslims. After completing his pledge of allegiance, Abu Bakr gave a speech as a welcome speech for the people's trust in him. Therefore, this study focuses on the content and meaning of Abu Bakr Ash-Siddiq's speech regarding the principles of his leadership. The method used is the literature study method. This research is in the type of qualitative. Stages of research carried out by collecting library sources, both primary and secondary. The result is that Abu Bakr Ash-Siddiq acts as a leader of worldly and religious power as well as a leader who brings and conveys religious teachings. Abu Bakr Ash-Siddiq's prophetic leadership values include; firmness, courage, generosity, justice and authority. The substance of Abu Bakr Ash-Siddiq's speech contained the principles and basics of leadership, which were not only applicable at the time, but also had a universal scope of meaning.